PENDIDIKAN KESEHATAN PERILAKU CERDIK DAN PATUH SEBAGAI UPAYA PENCEGAHAN DAN PENGENDALIAN HIPERTENSI PADA MASYARAKAT DI KELURAHAN MUARA RAPAK BALIKPAPAN - Rahmawati Shoufiah; Grace Carol Sipasulta; Sri Hazanah (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2025)
Hypertension is one of the most common non-communicable diseases (NCDs) suffered by the world's population and is a major risk factor for various serious complications, such as stroke, kidney failure, and coronary heart disease. The Indonesian Ministry of Health has introduced a behavioral change approach known by the acronyms CERDIK and PATUH as an educational effort in the prevention and control of non-communicable diseases, including hypertension. Through this community service activity, it is hoped that positive changes will be created in the aspects of community knowledge, attitudes, and actions towards hypertension prevention, thereby supporting government efforts to reduce the incidence of hypertension and improve the quality of life of the community. The method used is providing health education through interactive counseling, pre-test and post-test, question and answer discussions held for 2 days and attended by 47 participants. The results of the pre-test and post-test showed an increase in community knowledge after being provided with Health Education on CERDIK and PATUH Behavior as Efforts to Prevent and Control Hypertension in Muara Rapak Village, Balikpapan.